Quantification Of Sesquiterpene Compounds In Some Artemisia Species By Gas Chromatography-Mass Spectrometry And High-Performance Liquid Chromatography Methods (Applied Biological Research, 2023)
Artemisinin (quinzhees) and its derivatives is a natural compound isolated  from Artemisia annua which draws its interest in the treatment of drug resistant malaria. The current study was aimed to study the sesquiterpene compounds by using GCMS and to determine thecontents of artemisinin  derivative compounds. This paper also emphasized on the quantification of  artemether by using HPLC method from a few selected Artemisia species (A. annua, A. japonica, A. nilagirica, A. pallens and A. abrotanum) from different  localities of Karnataka (India). In GCMS the relative percentage and amount  of each component was calculated by comparing its average peak area to the  total area. Data handling was done using Xcaliber software. In HPLC  technique, the artemether content was established by Waters 510 Isocratic  System with C18 column. In total, 23 components were identified in GC-MS  with major constituents as arteannuin b (51%), davana ether (8.3%),  davanone (5%), β-eudesmol (72%), pallensin (27%) and cis-hydroxy davanone (85%). In HPLC, artemether was found in all plants in the range  of 0.6-6.0 mg, except A. jopanica. However, the present study validates the  ethno-medicinal use of artemisinin and its derivatives in malaria treatment.
Keywords: Artemether; Artemisia species; GC-MS; HPLC; sesquiterpene